DNase I-Functionalized Erythromycin-Encapsulated Chitosan Nanoparticles: A Dual-Action Treatment of Resistant Bacterial Infections and Biofilm Eradication - Srivastava, Saumya (Thapar Institute of Engineering and Technology, 2025)
The exponential growth of bacterial infections that are resistant to antibiotics and the persistence of biofilms have rendered medical treatment extremely challenging, often making conventional drugs insignificant. With the goal to solve this issue our study focuses on developing a dual- action nanocarrier system that can target both resistant bacterial cells and biofilm matrix. Using the ionic gelation process, a new formulation of erythromycin-loaded chitosan nanoparticles was made. These nanoparticles were further coated with a layer of chitosan–DNase I enzyme. This method is a gentle, efficient, and biocompatible way of producing nanoparticles. It uses electrostatic interactions between chitosan and tripolyphosphate (TPP). Four distinct batches of nanoparticles were first made by varying the concentrations of chitosan and the drug. Then, the most promising batch was selected based on the size of the particles, how effectively they encapsulated the drugs, and how rapidly they released the drugs. Batch S5, which had 0.3% chitosan, 0.5% erythromycin, and 0.45% TPP, had the best characteristics. It had a high encapsulation effectiveness (94.65%) and a particle size of 161.3 nm. Studies of drug release at pH levels of 1.2, 6.8, and 7.4 showed a sustained release profile, with increased release at pH. FTIR evaluation of the drug encapsulated nanoparticles confirmed that erythromycin was successfully encapsulated and DNase I was introduced to the surface. DLS and zeta potential analyses confirmed that the nanoparticles were stable and uniform, and XRD data indicated that the drug encapsulation modified the nanoparticles from crystalline to amorphous form. The antibacterial activity, tested using the micro broth dilution method against both E. coli and S. aureus, demonstrated that the enzyme-coated nanoparticle formulation (Batch S5) achieved over 90% growth inhibition, outperforming free erythromycin and blank nanoparticles. Additionally, antibiofilm activity, assessed via crystal violet staining, showed that Batch S7 was able to stop 92.19% of E. coli biofilm and 89.72% of S. aureus biofilm. This was much more active than free antibiotics (such erythromycin, streptomycin, and ampicillin) and even pure DNase I enzyme. This shows that giving an antibiotic and a biofilm-disrupting enzyme together works better than giving them separately. vi In conclusion, the DNase I–coated erythromycin-loaded chitosan nanoparticles developed in this study provide a promising dual-action strategy for combating both planktonic and biofilmassociated bacterial infections, particularly those caused by drug-resistant strains. This work offers a strong foundation for further in vivo studies and potential clinical translation.
Keywords: Erythromycin-Encapsulated; Chitosan Nanoparticles; Bacterial Infections; Biofilm Eradication; Resistant